Assessment of tree growth characters of multi purpose tree species planted underwasteland conditions - Jain, K. K.; Sharma, H.L. (Indian Journal of Agroforestry, 2020)
The present study was conducted at the Forestry Research Farm, Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur (M.P.) on 20 years old plantation of MPTs (year 1988) in Nelder’s Design. Before this, there was no tree plantation at this site and only grasses were growing naturally. As a consequence, this site was heavily grazed and overused. The soil was very poor and having a 8-9% slope with undulating topography. To develop this wasteland, a study was planned consisting of ten popular multipurpose tree species of this region viz., Pongamia pinnata (karanj), Azadirachta indica (neem), Acacia nilotica (babul), Eucalyptus cammaldulensis (eucalyptus), Cassia siamea (kassod tree), Albizia procera (safed siris), Dalbergia sissoo (sissoo), Melia azedarach (bakain), Leucacena leucocephala (subabul) and Acacia auriculiformis (Australian babul) were taken to evaluate their performance under variable spacing ranging from 1 m X 1 m to 10 m X 10 m. The tree growth measured in terms of diameter at breast height (dbh), tree height and the total cylindrical volume (m3) indicated dbh, as one of the major determinant of tree volume under the closer spacing i.e. 1 m X 1 m. The maximum dbh (22.44 cm) was observed in case of babul followed by bakain (20.05), which were significantly superior to neem (9.39) and karanj (7.01), whereas under wider spacing viz. 9 m X 9 m babul had the maximum dbh in comparison to other MPTs. However, the lowest dbh was found in karanj uniformly in all the spacing. For the development of wasteland the suitable species viz., Azadirachta indica, Acacia nilotica, Albizia procera, Dalbergia sissoo, Leucacena leucocephala and Pongamia pinnata could be appropriate due to their nitrogen fixing ability. The higher volume production can be obtained under wider spacing for the suitability of the local site conditions.